Methods and criteria for validating the multimodal functions of perinatal derivatives when used in oncological and antimicrobial applications - Silini, Antonietta R.; Ramuta, Taja Železnik; Pires, Ana Salomé; Banerjee, Asmita; Dubus, Marie; Gindraux, Florelle; Kerdjoudj, Halima; Maciulatis, Justinas; Weidinger, Adelheid; Wolbank, Susanne; Eissner, Günther; Giebel, Bernd; et al. (Frontiers in Bioengineering and Biotechnology, 2022)
Perinatal derivatives or PnDs refer to tissues, cells and secretomes from perinatal, or birth-associated tissues. In the past two decades PnDs have been highly investigated for their multimodal mechanisms of action that have been exploited in various disease settings, including in different cancers and infections. Indeed, there is growing evidence that PnDs possess anticancer and antimicrobial activities, but an urgent issue that needs to be addressed is the reproducible evaluation of efficacy, both in vitro and in vivo. Herein we present the most commonly used functional assays for the assessment of antitumor and antimicrobial properties of PnDs, and we discuss their advantages and disadvantages in assessing the functionality. This review is part of a quadrinomial series on functional assays for the validation of PnDs spanning biological functions such as immunomodulation, anticancer and antimicrobial, wound healing, and regeneration